2008
DOI: 10.1103/physrevd.77.085015
|View full text |Cite
|
Sign up to set email alerts
|

Self-tuning vacuum variable and cosmological constant

Abstract: A spacetime-independent variable is introduced which characterizes a Lorentz-invariant self-sustained quantum vacuum. For a perfect (Lorentz-invariant) quantum vacuum, the self-tuning of this variable nullifies the effective energy density which enters the low-energy gravitational field equations. The observed small but nonzero value of the cosmological constant may then be explained as corresponding to the effective energy density of an imperfect quantum vacuum (perturbed by, e.g., the presence of thermal mat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
278
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(284 citation statements)
references
References 61 publications
(136 reference statements)
6
278
0
Order By: Relevance
“…Ref. [1] and references therein). In addition, the matter energy-momentum tensor for the model universe is taken as that of a perfect fluid characterized by the energy density ρ M and isotropic pressure P M .…”
Section: Dynamics Of a Flat Frw Universementioning
confidence: 99%
See 3 more Smart Citations
“…Ref. [1] and references therein). In addition, the matter energy-momentum tensor for the model universe is taken as that of a perfect fluid characterized by the energy density ρ M and isotropic pressure P M .…”
Section: Dynamics Of a Flat Frw Universementioning
confidence: 99%
“…[1] in general terms. But a specific example was also given in terms of a four-form field strength F [3,4,5,6,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This numerical coincidence is impressive and also means that this model gets rid of fine tuning problem [8,9]. Actually, several authors have already suggested DE model with energy density proportional to Λ 3 QCD H in different physical contexts [15,16,17,18,19,20,21,39, 40] such as QCD trace anomaly, gluon condensate of quantum chromodynamics, modifying gravity and so on.…”
Section: Introductionmentioning
confidence: 96%